The Role of Ethics in Development: An Islamic Perspective - Elderşevi, Suheyib (İstanbul Sabahattin Zaim Üniversitesi, 2025)
This dissertation's is based on the conviction that the current environmental and socioeconomic crises—from the phenomenon of global warming to the extraordinary changes in the climate to poverty are the result of a profound moral crisis. Although religions are concerned about protecting the planet, yet it seems that the majority of those problems stem more from human immorality than from natural forces. The dissertation came in six chapters. It adopts a qualitative approach through document analysis strategies and case studies. A framework for sustainable development grounded in Islamic values was presented in this dissertation. It took into account a number of crucial elements that form the basis of advancement and sustainable life. Among these values are justice, social capital, reducing corruption, and reforming the earth. Each of these three values was elaborated in the dissertation. These values are frequently mentioned in Islamic sources due to their significant impact. The dissertation proves that the situation of sustainable development plans will be far better if these values are appropriately incorporated into the development scheme of any society. Moreover, the dissertation highlighted that shifting the development model from a pattern centered only on the individual to one that stresses the harmonious connection between the Creator, people, community, and nature is necessary to activate sustainable development. The dissertation also sheds light on the Nordic welfare model, which appropriately combines economic efficiency and social equality.

Bu çalışma, mevcut çevresel ve sosyoekonomik krizlerin, küresel ısınma, iklim değişiklikleri, yoksulluk ve eşitsizlik gibi sorunların temelinde derin bir ahlaki kriz olduğunu savunmaktadır. Dinler gezegenin korunması konusunda endişeler taşısa da, çevresel sorunların çoğunun doğal güçlerden değil, insan ahlaksızlığından kaynaklandığı belirtilmektedir. Çalışma, nitel bir yaklaşımı benimseyerek belge analizi ve vaka çalışmaları yöntemlerini kullanmıştır. İslamî değerlere dayalı bir sürdürülebilir kalkınma çerçevesi ortaya konulmuş ve bu çerçeve, iyi bir yaşamın ve ilerlemenin temel unsurlarını kapsamlı şekilde analiz etmiştir. Adalet, sosyal sermaye, yolsuzluğun azaltılması ve yeryüzünün ıslahı gibi temel değerler, İslam kaynaklarında sıkça vurgulanan ve toplumlar üzerindeki olumlu etkileri nedeniyle ön plana çıkan unsurlardır. Çalışma, bu değerlerin toplumların kalkınma planlarına entegre edilmesi durumunda sürdürülebilir kalkınma hedeflerine daha etkili bir şekilde ulaşılabileceğini savunmaktadır. Bununla birlikte, kalkınma modelinin birey merkezli bir yaklaşımdan birey, toplum, doğa ve Yaratıcı arasındaki uyumlu ilişkileri esas alan bir modele kaydırılmasının, sürdürülebilir kalkınmanın etkinleştirilmesi ve insan medeniyetinin ilerlemesi açısından zorunlu olduğu vurgulanmıştır. Çalışma ayrıca, İslam medeniyetinin sürdürülebilir yaşam fikrini nasıl yeniden şekillendirdiğine dair "zühd" kavramına odaklanmıştır. Son olarak, çalışma, ekonomik verimlilik ve sosyal eşitliği başarılı bir şekilde birleştiren İskandinav refah modelini detaylı olarak incelemiştir. Bu model, kalkınma açısından üstün nitelikleri nedeniyle seçilmiş ve incelenmiştir.
Ahlakın Kalkınmadaki Rolü: İslami Bir Bakış Açısı
Keywords: Sustainable Development; Islamic Values; Justice; Combating Corruption; Nordic welfare model; Sürdürülebilir Kalkınma; İslami Değerler; Adalet; Yolsuzlukla Mücadele; İskandinav Refah Modeli